Impact of Temperature Variation on Friction Behaviour of Rare Earth-Doped Diamond-like Carbon Coatings with Ionic Liquid Lubricants - Shaikh, Shahsharif (2023)
This research paper investigates the tribological performance of diamond-like carbon (DLC) coatings doped with rare earth metals (europium and gadolinium) as well as pure DLC lubricated with ionic liquid additives (trihexyltetradecylphosphonium bis(2-ethylhexyl) phosphate {[P66614][DEHP]} and 1-ethyl-3-methylimidazolium diethyl phosphate {[EMIM][DEP]}) in Polyalphaolefin 8 (PAO8). The study aims to examine the effect of temperature on the interaction between the coatings and additives by conducting tribological experiments using a block-on-disk setup at temperatures of 60 C, 80 C, and 100 C. The primary objective is to evaluate the performance of doped DLC coatings compared to pure DLC coatings with ionic liquid additives in the lubricant in boundary lubrication conditions at various high working temperature environments. The experiments reveal that doped DLC coatings with ionic liquid additives exhibit superior tribological performance compared to pure DLC coatings. The rare earth metal dopants play a positive role in the formation of a tribofilm on the surface of the coatings as it interacts with ionic liquids, resulting in a lower coefficient of friction (CoF). Temperature influences the performance of the coatings and additives. The CoF increases with temperature for pure DLC coatings, while for doped DLC coatings it was significantly less. These findings highlight the influence of temperature on the tribological behavior of DLC coatings. Overall, this study contributes valuable insights into the impact of rare earth metal dopants and ionic liquid additives on the tribological performance of DLC coatings under different temperature conditions. The results demonstrate the potential of utilizing doped DLC coatings with ionic liquid additives as an effective approach to enhance the performance of mechanical systems.